MANAJEMEN LABA, PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN SUSTAINABILITY REPORTING PERUSAHAAN MANUFAKTUR DI BEI - Sofiani Murni; Sri Ayem (Fakultas Bisnis UKDW, 2021)
ABSTRACTThe aim of this research is to obtain empirical evidence about the effects of earnings management and disclosure of Corporate Social Responbilty to Sustainability Reporting. Corporate Social Responbilty calculated with a control variable that is leverage, Growth, Roa and Sustainability Reporting projected with sustainability reporting disclosure index with is based on reporting standards Global Reporting Initiative (GRI) that the company discloses in annual reports and ongoing reports. The population in this study is all sub-sectors of manufacturing companies in Indonesia stock exchange (BEI). The total sample is 100 companies selected using the purposive sampling method issued annual reports for the period 2014-2018. Data to be tested using multiple linear regression analysis. The results of this research are: (1) Earnings management has a significant positive effect on sustainability reporting. (2) Leverage positively influences sustainability reporting. (3) Growth growth has a positive effect on sustainability reporting. (4) ROA has a positive effect on sustainability reporting.Keywords: earning management leverage, growth, ROA, sustainability reporting ABSTRAKPenelitian ini bertujuan untuk memperoleh bukti empiris mengenai pengaruh Manajemen Laba dan Pengungkapan Corporate Social Responsibility terhadap Sustainability Reporting. Corporate Social Responsibility dihitung dengan variabel control yaitu leverage, growth, ROA dan sustainability reporting diproyeksikan dengan sustainability reporting disclosure index yang didasarkan pada standar pelaporan Global Reporting Intitative (GRI) yang diungkapkan perusahaan dalam laporan tahunan dan laporan berkelanjutan. Populasi dalam penelitian adalah semua sub sector perusahaan manufaktur di bursa efek Indonesia (BEI). Total sampel adalah 100 perusahaan yang dipilih menggunakan metode purposive sampling yang mengeluarkan laporan tahunan selama periode tahun 2014-2018. Data untuk diuji dengan menggunakan analisis regresi linear berganda. Hasil dari penelitian ini adalah: (1) Manajemen laba berpengaruh positif signifikan terhadap sustainability reporting, (2) Leverage berpengaruh positif terhadap sustainability reporting, (3) Growth berpengaruh positif terhadap sustainability reporting. (4) ROA berpengaruh positif terhadap sustainability reporting.Kata kunci: manajemen laba, leverage, growth, ROA, sustainability reporting